MINERAL ISOGRADS AND METAMORPHIC ZONES OF THE ANGLESEY BLUESCHIST BELT, UK: IMPLICATIONS FOR THE METAMORPHIC DEVELOPMENT OF A NEOPROTEROZOIC SUBDUCTION-ACCRETION COMPLEX - Kawai T.; Maruyama S.; Windley B.F.; Terabayashi M.; Yamamoto H.; Isozaki Y. (My University, 2006)
The 560-550 Ma blueschists and associated rocks in Anglesey, UK were derived from a subduction-accretion complex. The blueschist unit is divided into three mineral zones by two newly mapped metamorphic isograds; zone I sub-greenschist facies, (crossite isograd), zone II blueschist facies, (barroisite isograd), zone III epidote-amphibolite facies. The zones and isograds dip gently to the east, and decrease in metamorphic grade from the central high-pressure zone III to lower grade zones II and I to the west and east. The P-T conditions estimated from zoned amphibole indicate an anticlockwise P-T path following adjustment to a cold geotherm. This path is well preserved in the compositional zoning of Na-Ca amphibole that have a core of barroisite surrounded by a rim of crossite, although this is only locally developed. The sense of subduction was to the east and exhumation to the west, as indicated by the metamorphic isograds. The symmetrical arrangement of the metamorphic zones with the deepest high-pressure rocks in the middle suggests an isoclinal antiformal structure that formed by wedge extrusion during exhumation in the subduction zone. © 2006 Blackwell Publishing Ltd.
Keywords: ANGLESEY; BLUESCHIST; MINERAL ZONES; P-T PATH; Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская